2010
DOI: 10.4038/tare.v11i0.1783
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of two endemic threatened <i>Cryptocoryne</i> species of Sri Lanka

Abstract: An efficient protocol was developed for the micropropagation of Cryptocoryne beckettii and Cryptocoryne bogneri, two endemic threatened aquatic herbs of Sri Lanka, highly valued as aquarium plants. Rhizomes of C. beckettii and C. bogneri were established on full strength Murashige and Skoog (MS) medium with 3% sucrose and regenerated shoots were cultured on MS medium supplemented with combinations of 6-benzylaminopurine (BAP) 2, 5, 8, 10 mg l -1 and 0.1 mg l -1 indole acetic acid (IAA) for multiple shoot regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…nana (Kanchanapoom et al, 2012), Cryptocoryne lucens (Kane et al, 1990), Cryptocoryne sp. (Herath et al, 2008), Cryptocoryne wendtii and C. becketti (Sheeja et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…nana (Kanchanapoom et al, 2012), Cryptocoryne lucens (Kane et al, 1990), Cryptocoryne sp. (Herath et al, 2008), Cryptocoryne wendtii and C. becketti (Sheeja et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro rooting, shoots subjected to 1.0 mg/l NAA treatment produced an average of 36.00 ± 4.63 roots and root length at 26.02 ± 0.70 mm was significantly different from other treatments (Table 2 and Figure 2C). The use of NAA in enhancing the root formation has also been observed in Cryptocoryne beckettii and Cryptocoryne bogneri [21]; Kinnow [22] and Hippeastrum johnsonii [23].…”
Section: Effects Of Naa On Root Induction In Vitromentioning
confidence: 95%
“…The results of this study indicated that plant growth regulator supplementation is essential for the micropropagation of C. wendtii. The effectiveness of BAP in shoot bud differentiation has been documented in the number of plants [15,7]. Wang et al [16] reported that the presence of 3.0 mg/l BAP in the medium effectively increased the number of regenerated shoots of Scipus robustus an emergent hydrophyte.…”
Section: Effects Of Cytokinins On Direct Shoot Organogenesis Induction From Shoot Tip Explants In Vitromentioning
confidence: 99%